The Warburg Institute Iconographic Database - Warburg Institute (2011)
[Dt.:] Die Warburg Institute Iconographic Database beinhaltet Bilder aus der Photographischen Sammlung und der Bibliothek des Instituts. Die Datenbank kann nach ikonographischen Kategorien und nach Künstler, Datum und Ort durchsucht werden. - [Engl.:] The Warburg Institute Iconographic Database contains digitised images from the Institute's Photographic Collection and Library. Search by iconographic keywords or browse the iconographic classification system. To search by artist, date, location, or other parameters, you can use the advanced search menu. The iconographic classification system of the database is based on that of the Warburg Institute Photographic Collection. Please note that the database is not the digital equivalent of the Photographic collection.